2008
DOI: 10.3386/w13817
|View full text |Cite
|
Sign up to set email alerts
|

Choice, Price Competition and Complexity in Markets for Health Insurance

Abstract: Column 1: the number of choice is represented by a continuous variable Column 2: the number of choice is represented by one dummie variable (> 55 plans) Column 3: the number of choices is represented by dummies (Choice: [30-49],[50-55], [56-60], [61-70]) Column 4: distinguishes the number of big firms and fringe firms Column 5: uses the inverse of the Herfindahl index Column 6: is run on the subsample of those who have not subscribed to a supplementary health insurance contract Column 7: Instrumenting the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 16 publications
8
107
0
2
Order By: Relevance
“…Several studies have shown that consumers of health insurance exhibit price-sensitivity. Historically, the majority of this evidence has come from the United States [7][8][9][10], however more recently similar effects have been found in certain European (Dutch, German, and Swiss) markets [11][12][13][14][15][16]. However, price sensitivity in the Dutch system has been found to be comparatively low [11,17], potentially the result of historically more robust risk equalization, which helps limit price variation between insurers.…”
Section: International Evidence On Consumer Mobilitymentioning
confidence: 89%
“…Several studies have shown that consumers of health insurance exhibit price-sensitivity. Historically, the majority of this evidence has come from the United States [7][8][9][10], however more recently similar effects have been found in certain European (Dutch, German, and Swiss) markets [11][12][13][14][15][16]. However, price sensitivity in the Dutch system has been found to be comparatively low [11,17], potentially the result of historically more robust risk equalization, which helps limit price variation between insurers.…”
Section: International Evidence On Consumer Mobilitymentioning
confidence: 89%
“…The distribution of educational level in our sample is quite representative of the general population. The percentages of individuals with good/very good health and of people with supplemental insurance coverage are slightly smaller than those exhibited in national representative surveys carried out during the same time period [28]. The whole study sample (including health care professionals) included 1594 people and is described in the last four columns of Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…A practical implication that can be derived from the findings is that consumers need help navigating the health insurance decision (Frank and Lamiraud 2009;Hanoch and Rice 2011). As the first release of a series of Cooperative Extension consumer health insurance literacy programs, Smart Choice TM is designed to reduce confusion, increase capability, and increase confidence of consumers as they make health insurance plan decisions (Russell et al 2014).…”
Section: Implications and Conclusionmentioning
confidence: 97%
“…Although the ACA provides greater consumer protection, researchers and practitioners advocate for improved health insurance education (Frank and Lamiraud 2009;Hanoch and Rice 2011;Hibbard et al 2002;Wroblewski 2007). Several federal agencies (e.g., Centers for Medicare and Medicaid [CMS]) and national organizations such as Families USA, Enroll America, Consumers Union, and Cooperative Extension are working to increase consumers' health insurance literacy and bring momentum to this issue.…”
Section: Addressing Health Insurance Literacy: Smart Choice Health Inmentioning
confidence: 98%